The ESRP1-GPR137 axis contributes to intestinal pathogenesis - Lukas Franz Mager; Viktor Hendrik Koelzer; Regula Stuber; Lester Thoo; Irene Keller; Ivonne Koeck; Maya Langenegger; Cedric Simillion; Simona P Pfister; Martin Faderl; Vera Genitsch; Irina Tcymbarevich; et al. (eLife, 2017)
Aberrant alternative pre-mRNA splicing (AS) events have been associated with several disorders. However, it is unclear whether deregulated AS directly contributes to disease. Here, we reveal a critical role of the AS regulator epithelial splicing regulator protein 1 (ESRP1) for intestinal homeostasis and pathogenesis. In mice, reduced ESRP1 function leads to impaired intestinal barrier integrity, increased susceptibility to colitis and altered colorectal cancer (CRC) development. Mechanistically, these defects are produced in part by modified expression of ESRP1-specific Gpr137 isoforms differently activating the Wnt pathway. In humans, ESRP1 is downregulated in inflamed biopsies from inflammatory bowel disease patients. ESRP1 loss is an adverse prognostic factor in CRC. Furthermore, generation of ESRP1-dependent GPR137 isoforms is altered in CRC and expression of a specific GPR137 isoform predicts CRC patient survival. These findings indicate a central role of ESRP1-regulated AS for intestinal barrier integrity. Alterations in ESRP1 function or expression contribute to intestinal pathology.